A high proportion of leucine is required for optimal stimulation of the rate of muscle protein synthesis by essential amino acids in the elderly - Katsanos, Christos S; Kobayashi, Hisamine; Sheffield-Moore, Melinda; Aarsland, Asle; Wolfe, Robert R (American journal of physiology: endocrinology and metabolism, 2006)
Departments of 1 Surgery and Shriners Hospitals for Children-Galveston, 3 Internal Medicine, and 4 Anesthesiology, University of Texas Medical Branch, Galveston, Texas; and 2 AminoScience Laboratories, Ajinomoto Company, Incorporated, Kawasaki, Japan Submitted 6 October 2005 ; accepted in final form 17 February 2006 This study was designed to evaluate the effects of enriching an essential amino acid (EAA) mixture with leucine on muscle protein metabolism in elderly and young individuals. Four (2 elderly and 2 young) groups were studied before and after ingestion of 6.7 g of EAAs. EAAs were based on the composition of whey protein [26% leucine (26% Leu)] or were enriched in leucine [41% leucine (41% Leu)]. A primed, continuous infusion of L -[ ring - 2 H 5 ]phenylalanine was used together with vastus lateralis muscle biopsies and leg arteriovenous blood samples for the determinations of fractional synthetic rate (FSR) and balance of muscle protein. FSR increased following amino acid ingestion in both the 26% (basal: 0.048 ± 0.005%/h; post-EAA: 0.063 ± 0.007%/h) and the 41% (basal: 0.036 ± 0.004%/h; post-EAA: 0.051 ± 0.007%/h) Leu young groups ( P < 0.05). In contrast, in the elderly, FSR did not increase following ingestion of 26% Leu EAA (basal: 0.044 ± 0.003%/h; post-EAA: 0.049 ± 0.006%/h; P > 0.05) but did increase following ingestion of 41% Leu EAA (basal: 0.038 ± 0.007%/h; post-EAA: 0.056 ± 0.008%/h; P < 0.05). Similar to the FSR responses, the mean response of muscle phenylalanine net balance, a reflection of muscle protein balance, was improved ( P < 0.05) in all groups, with the exception of the 26% Leu elderly group. We conclude that increasing the proportion of leucine in a mixture of EAA can reverse an attenuated response of muscle protein synthesis in elderly but does not result in further stimulation of muscle protein synthesis in young subjects. nutrition; sarcopenia; stable isotopes Address for reprint requests and other correspondence: C. S. Katsanos, Metabolism Unit, Shriners Burns Hospital, 815 Market St., Galveston, TX 77550 (e-mail: cskatsanatutmb.edu )